Russia, the Islamic World, and the New World Order: Implications for Indonesia - Rizki Damayanti; Hizra Marisa; Marsya Pramesthi Dayusaputra (Andalas Journal of International Studies (AJIS), 2025)
The emergence of a new world order is raising its involvement in the relationship between Russia and the Islamic world, which is also of significant relevance for Indonesia given its position as a bridge to Russiaâ€™s broader pivot to the East. This research aims to analyze how Russiaâ€™s growing ties with Islamic nations impact global power structures and influence Indonesiaâ€™s foreign policy and strategic interests. Using Rosenauâ€™s foreign policy theory that conceptualizes state behavior as an adaptive response to changes in the external environment in order to seek survival, this study implies a qualitative approach to define Russiaâ€™s geopolitical rationale. The analysis draws on primary and secondary sources including policy documents, official statements, scholarly articles, and interviews with representatives from the Russian Embassy in Indonesia and the Indonesian Ministry of Foreign Affairs. The findings reveal that Russiaâ€™s growing engagement with the Islamic world forms part of broader strategy to counter Western domination and establish a multipolar world order through economic, military, and diplomatic initiatives. This has made Russia positioned itself as a central power broker across the Middle East, North Africa, and Asia. Therefore, as a prominent Muslim-majority nation and a key ASEAN member, Russiaâ€™s ongoing developments carry strategic implications for Indonesia. Russiaâ€™s expanding role offers opportunities for Indonesia that goes along with Indonesiaâ€™s â€œfree and activeâ€ foreign policy but simultaneously generating challenges by increasing external pressure on Indonesiaâ€™s ability to maintain that posture. Consequently, Indonesia must actively navigate strategic and balanced foreign policy to enhance its diplomatic leverage, while maintaining regional stability and promote its national interest.